PENGEMBANGAN BAHAN AJAR BUKU SAKU KIMIA DENGAN PENDEKATAN CHEMO-ENTERPRENNEURSHIP (CEP) BERORIENTASI GREEN CHEMISTRY PADA MATERI ASAM BASA - emylia nirwana; elvi yenti (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2021)
AbstractThe lack of learning resource availability developed in the school constituted a background of this research.  Thus, developing chemistry pocket book teaching material with Green Chemistry oriented Chemo-Entrepreneurship approach on Acid Base Lesson was designed in this research.  4-D development model was used in this research until Develop stage.  The subjects of this research were a media expert lecturer, a material expert teacher, 2 Senior High School teachers for media practicality test, and 10 students at State Senior High School 4 Pekanbaru for knowing the response to the media.  Data collected in this research were in the forms of interview and questionnaire.  Instruments of collecting data were validity and response questionnaires.  The data obtained were analyzed by using qualitative and quantitative descriptive analysis techniques.  Based on the research findings, the media validation percentages were 91.30% by the material expert and 89.28% by the media expert with very valid assessment criteria, the percentage of teacher practicality test was 95% with very practical criterion.Keywords : Pocket Book, Chemo-Entrepreneurship Approach, Green Chemistry, Acid Base